3D strain evolution in concrete using in situ X-ray computed tomography testing and digital volumetric speckle photography. (February 2019) - Mao, Lingtao; Yuan, Zexun; Yang, Min; Liu, Hongbin; Chiang, Fu-pen
Highlights: Digital volumetric speckle photography, a 3D strain mapping technique, is presented. DVSP is applied to the investigation of 3D displacement and strain distribution in the concrete specimen under compression. The regions of strain localization and their evolutions in the concrete specimen were revealed from the strain distribution. Abstract: The fracture process for concrete materials under compression is a complex three-dimensional phenomenon that occurs as a result of material heterogeneity and complicated mixed-mode cracking mechanisms. To understand the failure mechanism of concrete, it is necessary to have a technique that can probe the interior of the material as it is being loaded. In this paper, we use an industrial computed tomography (CT) system to obtain the volumetric image of a concrete circular cylinder under compression by taking advantage of the ability of X-rays to penetrate opaque materials. In addition, we employ a newly developed 3D strain analysis technique called digital volumetric speckle photography (DVSP) to calculate the displacement and strain distribution in two longitudinal meridian sections and a midpoint transverse section of the specimen. We are able to reveal the regions of strain localization and their evolutions, which eventually lead to the failure of the specimen.